Novel Bis-1,3,4-Thiadiazoles Derivatives: Synthesis, Spectroscopic Characterization, DFT Calculations and Evaluation of their Antimicrobial and Antioxidant Activities - Çakmak, Şükriye; Çavuş, Muhammet (Cumhuriyet University, 2023)
Two new, bis-1,3,4-thiadiazoles derivatives (I and II), were prepared by cyclization reaction of oxalic acid with N-alkyl/allyl thiosemicarbazides and phosphorous oxychloride (POCl3). Then the newly prepared products screened for their antimicrobial and antioxidant activities. The biological activity results shown that tested compounds exhibited effective antibacterial activity against six different bacteria. However, the compound II demonstrated greater ABTS˙+ scavenging ability. The characterization of the synthesized molecules was done by FT-IR, 1H NMR, 13C NMR spectroscopic methods and elemental analysis. Moreover, the experimental FT-IR and NMR spectra of the molecules were compared with the results calculated at the cc-pvtz, 6-311g(2d,2p), and 6-311++g(2d,2p) levels of theory. The effect of substituted groups on the spectral and electronic properties of the compounds was investigated. NCI and QTAIM analyses were performed to examine the effects of allyl group and intramolecular interactions on σ and π bonds. How the N-H bonds of the substituted groups affect the bond degrees was investigated using Fuzzy, Laplacian and Mayer approaches, and the relationship of the data with the antioxidant properties of the compounds was examined. In addition, the relationship between bond stretching force constant and intrinsic bond strength index, electron density, and delocalization index for some bonds was revealed.
Keywords: Bis-thiadiazoles; Biological activity; DFT; IBSI; Force constant (FC); Mantar Bilimi; Farmakoloji ve Eczacılık; Tıbbi; Bis-thiadiazoles; Biological activity; DFT; IBSI; Force constant (FC).; Biyoloji; Kimya